(untitled) (World Science, 2021)
The article presents the prospects for the production and application of carbon-containing nanomaterials used in nanotechnology. These materials include graphene, carbon nanoparticles, and fullerenes. They can be, used, as dielectric, semiconducting, conductive, including superconducting materials. The article also expressed an opinion on the method of obtaining fullerene.